2010
DOI: 10.1097/hjh.0b013e32833c20eb
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of acute and sustained cyclosporine and tacrolimus on sympathetic nerve activity

Abstract: Sympathetic overactivity plays a role in the acute hypertensive action of cyclosporine. Cyclosporine given during 2 weeks increases blood pressure and suppresses MSNA, possibly by volume retention. Tacrolimus, in the presently applied dosages, does not cause hypertension or sympathetic overactivity. However, sustained tacrolimus also suppresses sympathetic activity, the reason of which is unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 40 publications
(55 reference statements)
2
20
0
3
Order By: Relevance
“…This is most likely due to differences in their binding proteins; indeed, the complex between the drug and the binding protein has also been shown to be biologically active (12). Third, different mechanisms appear to play a role in the acute hypertensive effects of CNIs compared with their more chronic effects (13). Fourth, CNI-induced hypertension with preserved kidney function should be distinguished from CNI-induced nephrotoxicity, which is also associated with hypertension.…”
Section: Calcineurin Inhibitor–induced Hypertensionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is most likely due to differences in their binding proteins; indeed, the complex between the drug and the binding protein has also been shown to be biologically active (12). Third, different mechanisms appear to play a role in the acute hypertensive effects of CNIs compared with their more chronic effects (13). Fourth, CNI-induced hypertension with preserved kidney function should be distinguished from CNI-induced nephrotoxicity, which is also associated with hypertension.…”
Section: Calcineurin Inhibitor–induced Hypertensionmentioning
confidence: 99%
“…Although some studies found CNIs to increase plasma renin activity (31, 32), others observed suppressed levels (13, 33, 34). Some studies showed that CNIs inhibit the mineralocorticoid receptor, and this effect was held to be responsible for signs of hypoaldosteronism such as hyperkalemia and acidosis (35, 36).…”
Section: Vascular Effects Of Calcineurin Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…4). Possible mechanisms of the persistent prolonged baroreflex latency despite normalization of renal function including cardiac status, antihypertensive and immunosuppressive medication, and transplant vintage [19,31] remain to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Klein и соавт. [35] изучали влияние циклоспорина и такро-лимуса на активность постганглионарных симпати-ческих волокон в мышцах у практически здоровых лиц. Кратковременное назначение такролимуса вызывало дозозависимое увеличение активности пост ганглионарных нервных волокон, сопровожда-лось увеличением ЧСС и уровней АД.…”
Section: ингибиторы кальциневринаunclassified